2022
DOI: 10.3390/life12081227
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Environment on the Evolution and Proliferation of Protocells of Increasing Complexity

Abstract: The formation, growth, division and proliferation of protocells containing RNA strands is an important step in ensuring the viability of a mixed RNA–lipid world. Experiments and computer simulations indicate that RNA encapsulated inside protocells can favor the protocell, promoting its growth while protecting the system from being over-run by selfish RNA sequences. Recent work has also shown that the rolling-circle replication mechanism can be harnessed to ensure the rapid growth of RNA strands and the probabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…Several experiments have shown that both ribonucleotides [ 6–8 ] and deoxy-ribonucleotides [ 9 , 10 ] can be spontaneously created in prebiotic environments. Non-enzymatic processes of concatenation and template-directed primer extension, albeit with [ 11 , 12 ] or without [ 13 ] activated RNA nucleotides, along with environmental cycling [ 14 , 15 ] give rise to long RNA polymers that can fold into complex secondary structures [ 16 ]. It seems plausible that the first ribozymes emerged by chance through such processes, as a result of extensive sampling of the sequence space through error-prone replication [ 17 ] in a prebiotic environment.…”
Section: Introductionmentioning
confidence: 99%
“…Several experiments have shown that both ribonucleotides [ 6–8 ] and deoxy-ribonucleotides [ 9 , 10 ] can be spontaneously created in prebiotic environments. Non-enzymatic processes of concatenation and template-directed primer extension, albeit with [ 11 , 12 ] or without [ 13 ] activated RNA nucleotides, along with environmental cycling [ 14 , 15 ] give rise to long RNA polymers that can fold into complex secondary structures [ 16 ]. It seems plausible that the first ribozymes emerged by chance through such processes, as a result of extensive sampling of the sequence space through error-prone replication [ 17 ] in a prebiotic environment.…”
Section: Introductionmentioning
confidence: 99%
“…Several experiments have shown that both ribonucleotides [6, 7, 8] and deoxy-ribonucleotides [9, 10] can be spontaneously created in prebiotic environments. Non-enzymatic processes of concatenation and template-directed primer extension, albeit with [11, 12] or with-out [13] activated RNA nucleotides, along with environmental cycling [14, 15] give rise to long RNA polymers that can fold into complex secondary structures [16]. It seems plausible that the first ribozymes emerged by chance through such processes, as a result of extensive sampling of the sequence space through error-prone replication [17] in a prebiotic environment.…”
Section: Introductionmentioning
confidence: 99%